2014
DOI: 10.1186/s12879-014-0667-0
|View full text |Cite
|
Sign up to set email alerts
|

HIV patients with latent tuberculosis living in a low-endemic country do not develop active disease during a 2 year follow-up; a Norwegian prospective multicenter study

Abstract: BackgroundInterferon-γ release assays (IGRA) serve as immunodiagnostics of tuberculosis (TB) infection to identify individuals with latent TB infection (LTBI) eligible for preventive anti-TB therapy. In this longitudinal study of HIV-infected LTBI patients we have observed for possible progression to active TB as well as evaluated repeated IGRA testing in a TB low-endemic setting.MethodsQuantiFERON TB-Gold In-tube® assay (QFT), TB-SPOT.TB® (TSPOT) and tuberculin skin test (TST) were performed on 298 HIV-patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 31 publications
2
32
1
Order By: Relevance
“…None of the QFT-IT positive patients who completed at least 6 months of IPT developed active TB during the 3-year follow-up period. The effectiveness of QFT-IT-guided LTBI treatment in this study was consistent with the results of a previous Norwegian study (15); however, the risk of TB exposure during the follow-up period in our cohort might be greater because of the higher prevalence of TB in the Thai population. The use of both QFT-IT and TST at the initial screening enabled us to categorize patient groups with concordant and discordant test results and allow for the comparative evaluation of test performance.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…None of the QFT-IT positive patients who completed at least 6 months of IPT developed active TB during the 3-year follow-up period. The effectiveness of QFT-IT-guided LTBI treatment in this study was consistent with the results of a previous Norwegian study (15); however, the risk of TB exposure during the follow-up period in our cohort might be greater because of the higher prevalence of TB in the Thai population. The use of both QFT-IT and TST at the initial screening enabled us to categorize patient groups with concordant and discordant test results and allow for the comparative evaluation of test performance.…”
Section: Discussionsupporting
confidence: 82%
“…Considering the unknown benefit of serial IGRA testing and associated costs (8,15), we utilized TST as the subsequent test in patients with initial negative QFT-IT and non-reactive TST results (i.e., group 4). Neither TST conversion nor active TB case was detected for patients in this group during the follow-up period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Pullar et al 2014). Other example is bacterial confirmation which is not always feasible in children.…”
Section: Biomarkers To Predict Disease Progressionmentioning
confidence: 99%
“…In a prospective cohort study in lowendemic setting using QuantiFERON TB-Gold In-tube ® essay (QFT) to measure interferon-gamma (IFN-γ) level in LTBI/HIV co-infected patients on preventive treatment, it was found that the conversion of QFT to negative independent of the preventive anti-TB treatment indicating false positive results therefore QFT is unreliable in monitoring LTBI preventive treatment efficacy in TB low-endemic setting (Pullar et al 2014). Indeed, attempts were made to improve the reliability of diagnostic tool as well as to know the factors that contribute to false positive or false negative results.…”
Section: Biomarkers To Predict Disease Progressionmentioning
confidence: 99%